THERMALLY CLEAVABLE HYBRID MATERIALS - Constantin Gaina; Oana Ursache; Viorica Gaina (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Thermally cleavable hybrid materials were prepared by the Diels-Alder cycloaddition reaction of poly(vinyl furfural) to N phenylmaleimido-N’-(triethoxysilylpropyl)urea followed by the sol-gel condensation reaction of trietoxysilyl groups with water and acetic acid. Thermal and dynamic mechanical analysis, dielectric and FTIR spectroscopy were used to characterize the structure and properties of the composites. The size of the inorganic silica particles in the hybrid material varied dependent on the silica content. The DSC study of the prepared materials revealed that the cleavage process of the formed cycloadducts takes place at temperatures varying between 143-165°C and is an endothermic process.